Collaborative writing as inquiry - Speedy, Jane, 1954-; Wyatt, Jonathan (Cambridge Scholars Publishing, 2014)
"Collaborative Writing as Inquiry is a new and overdue contribution to the recently burgeoning literature on writing as a branch of qualitative inquiry. The book places a diversity of approaches to collaborative writing alongside each other, and explores these methods and the spaces between them as critical arts-based inquiry practices within the social sciences. It is not intended or written as any kind of a handbook, more of a scrapbook, containing summative and rich prologues to each section, and substantive chapters (some adapted from work previously published in international peer-reviewed journals), fragments and snippets of 'writing in progress', as well as more extensive excursions into a range of approaches to writing collaboratively, including: collective biography; call and response (to people, to landscapes and to 'what happens' in the writing spaces); 'take three words'; poetic writing; and writing in scholarly communities and/or on retreat. This book illuminates, investigates and interrogates these emergent spaces, particularly as a critical gesture towards the individualised, market-driven agendas and neo-liberal practices of the contemporary academy"--Provided by publisher